Carbon vacancies in Ti2CT2 MXenes: defects or a new opportunity?. Issue 47 (23rd November 2017) - Hu, Tao; Yang, Jinxing; Wang, Xiaohui
Abstract : Carbon vacancies that are usually considered as defects substantially endow MXenes with improved flexibility and enhanced electronic conductivity. Abstract : Carbon vacancies are commonly present in two-dimensional (2D) MXenes that hold promise in a variety of applications whereas their behavior remains unknown. Here we report on the influence of carbon vacancies on the structural stability, electronic properties and stiffness of MXenes by taking Ti2 CT2 (T = O, F, and OH) as an example. According to the first-principles calculations, the formation energies of carbon vacancies in MXenes are lower than those in other typical 2D materials including graphene and MoS2, in combination with high migration energies. These two features mean that carbon-vacant MXenes are thermodynamically and dynamically stable as further evidenced by the absence of structural reconstruction both in the ground state and at ambient temperature. Interestingly, carbon vacancies that are usually considered as defects substantially offer a new opportunity on at least two aspects: enhanced electronic conduction and reduced stiffness corresponding to improved flexibility. The localized states in the vicinity of the Fermi level introduced by carbon vacancies account for the prominent metallic characteristics in carbon-vacant Ti2 CT2 MXenes.